Dampak Perlokusi pada Mitra Tutur dalam Tindak Tutur Direktif Bahasa Jepang - Sayoga, Afrida Nurizka (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2025)
This research aim is to describe the perlocution impact of directive speech on Japanese interaction using the theory of directive speech acts by Searle (1979), perlocution effect by Haryadi (2003) and perlocution impact by Oktaviyani (2021). The method used is descriptive qualitative with listening and recording as a technique to collect research data. A movie titled Linda Linda Linda used as data source. The data is in the form of directive speech act that contains perlocution of all characters from the movie: a total of 37 data classified into 3 forms namely; a) command (22 data), b) request (6 data), c) suggestion (9 data). A command form with functions including: pleading (1 data), request (11 data), command (5 data), ask (2 data) and prohibition (3 data). A request form with function including: pleading (4 data) and request (2 data). Suggestion form with function to suggest (9 data). The research found 18 data of positive perlocution and 19 data of negative perlocution. Based on the impact, 8 data of changing speech partner’s mood, 24 data of speech partner perform an action, and 5 data of speech partner avoiding something. The conclusion of this research is 1) positive perlocution is produced from suggestion sentences in the form of suggest with the impact of perform an action, 2) negative perlocution is produced from command sentences in the form of request with the impact of changing the mood to be irritated, perform an action unwillingly, and avoiding the command.